(untitled) (Al-Qamar, 2022)
Islam is a complete code of life. It gives solution to all contemporary issues. It is the distinguish feature of Islam that provides the solutions of every problem rightly from its beginning to till the Day of Judgment. Whenever a new issue arises in Muslim community, the Islamic Jurists try to solve it in the light of Qurān & Sunnah. If the problem is not directly resolved through both these primary sources, the Jurists try to find its solution from secondary sources like Ijtihād and Qiyās etc. Islam has left no problem unsolved. As the time goes on, new problems arise and they are solved by the Mujtahidins. Therefore, it is the distinguished feature of Islam to address and solve all matters of every age. Islam has this distinguished feature due to Ijtihād and Qiyās. In this article, the role of Ijtihād and Qiyās will be discussed in solving the current issues of every age.